2022
DOI: 10.3390/molecules27041363
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of the Extraction of Proanthocyanidins from Grape Seeds Using Ultrasonication-Assisted Aqueous Ethanol and Evaluation of Anti-Steatosis Activity In Vitro

Abstract: Conventional extraction methods of proanthocyanidins (PAC) are based on toxic organic solvents, which can raise concerns about the use of extracts in supplemented food and nutraceuticals. Thus, a PAC extraction method was developed for grape seeds (GS) and grape seed powder using food-grade ethanol by optimizing the extraction conditions to generate the maximum yield of PAC. Extraction parameters, % ethanol, solvent: solid (s:s) ratio, sonication time, and temperature were optimized by the central composite de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 66 publications
2
9
0
Order By: Relevance
“…Nevertheless, as the extraction time increases beyond the optimal time, CT begins to decrease, possibly due to CT's transformation into anthocyanins. A comparable trend has been stated by Lv et al [60] , Dzah [24] , and Thilakarathna and Rupasinghe [61] on CT extraction using ultrasound. In terms of extraction time and TPC, it was observed that the influence was significant ( p < 0.05), as shown in Table 3 , and a quadratic effect was observed, as seen in the RS and perturbation plot ( Fig.…”
Section: Resultssupporting
confidence: 85%
“…Nevertheless, as the extraction time increases beyond the optimal time, CT begins to decrease, possibly due to CT's transformation into anthocyanins. A comparable trend has been stated by Lv et al [60] , Dzah [24] , and Thilakarathna and Rupasinghe [61] on CT extraction using ultrasound. In terms of extraction time and TPC, it was observed that the influence was significant ( p < 0.05), as shown in Table 3 , and a quadratic effect was observed, as seen in the RS and perturbation plot ( Fig.…”
Section: Resultssupporting
confidence: 85%
“…PACs are oligomers or polymers of flavan-3-ol molecules linked via inter-flavan linkages. Oligomeric and polymeric PACs predominantly consist of catechin and epicatechin monomers [ 23 , 24 ]. As PACs are polymers, they cannot always be represented by a constant molecular weight or molecular formula.…”
Section: Discussionmentioning
confidence: 99%
“…The interest in utilizing proanthocyanidins in the pharmaceutical industry has considerably increased over time with the discovery of their beneficial functions [ 27 ]. One possible approach is via skin application and incorporation into dermal formulations, such as polymeric films, which offer many advantages in terms of effective drug delivery and improved patient compliance [ 19 , 20 ].…”
Section: Discussionmentioning
confidence: 99%